Ocean thermohaline circulation and sedimentary 231Pa/230Th ratio - Marchal, Olivier; François, Roger; Stocker, Thomas F.; Joos, Fortunat (Paleoceanography, 2000)
Holocene sediments from the Atlantic are characterized by 231Pa/230Th ratios below the production ratio of the two radionuclides in the water column (0.093), whereas Holocene sediments from the Southern Ocean have 231Pa/230Th > 0.093. This pattern of 231Pa deficit and excess was ascribed to southward 231Pa export from the Atlantic by the Atlantic thermohaline circulation (THC) as Pa is scavenged less efficiently by marine particles and more effectively transported by the THC than Th. The same pattern is observed in deposits of the Last Glacial Maximum (LGM), which led to a previous contention that the THC strength did not vary markedly through the last glacial termination. Here we embed a description of trace metal scavenging into a zonally averaged, circulation-biogeochemistry ocean model to explore the sensitivity of 231Pa/230Th in Atlantic and Southern Ocean sediments to THC changes. Our results show that the production of biogenic opal (which, unlike other marine particles, poorly fractionates Th and Pa) in the Southern Ocean water column determines the spatial pattern of the sensitivity. Also, 231Pa/230Th increases in the North Atlantic but changes little in the South Atlantic and decreases in the Southern Ocean as THC is reduced. The mean 231Pa/230Th of the whole Atlantic is therefore less sensitive to THC changes than the mean 231Pa/230Th of the North Atlantic. The current uncertainties in Atlantic mean 231Pa/230Th are too large to rule out a twofold reduction of the THC at the LGM. However, the increase in North Atlantic mean 231Pa/230Th simulated in response to a twofold THC reduction is larger than the observed change in the North Atlantic mean 231Pa/230Th from the LGM to Holocene. Comparing this change with the modeled sensitivity of North Atlantic 231Pa/230Th to THC variations indicates that the THC at the LGM could not have been reduced by >30% of its present strength. Experiments of transient THC changes indicate that high-resolution 231Pa/230Th records from North Atlantic sediments could ...